Analysis of Problem Solving Ability Students Mathematis PGMI UINSU Based Zone of Proximal Development Of Students Primary School - Wandini, Rora Rizky; Damanik, Emeliya Sukma Dara; Iskandar, Wahyu (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The purpose of this study is to describe the problem solving ability of students mathematis work PGMI based object ZPD primary school students, with a descriptive qualitative research methods. Insendental sampling using sampling at half PGMI student V. Data were collected through a test which is divided into two, namely the initial test and final test and through observation and interviews. With a simple statistical analysis results that students who have a high initial knowledge to solve problems working mathematis on objects of primary school students aged 6-10 years by ZPD, also have mathematis problem solving skills are good. While students who have a low initial knowledge unable to solve problems working mathematis on objects of primary school students aged 6-10 years by ZPD